PEMANFAATAN METODE ITERATED FUNCTION SYSTEM (IFS) PADA PEMBANGKITAN KURVA NAGA - Suny, Vian Hafid; Purnomo, Kosala Dwidja; Ubaidillah, Firdaus (Jurusan Matematika FMIPA Universitas Jember, 2020)
Fractals have two types, namely fractals sets (artificial fractals) and natural fractals. Each type of fractal has a variety of fractal objects. One of the fractal objects is the Dragon Curve. Fractal objects can be generated through two methods, namely the Lindenmayer System (L-System) and the Iterated Function System (IFS). In previous studies, the Dragon curve can be generated through the L-System approach. The method is to start from determining the rotation angle, then determining the initial string, and the last one, which is determining the production rules. In this study, the Dragon curve is generated using IFS with Affine Transformation. The Affine transformation used in this study is dilation and rotation. Some variation is given on the scale of dilation and rotation angle. The variation is using a fixed angle with a variety of scale and using a fixed scale with a variation of angle. Each variation gives a different effect. This influence results in a varied visualization of the Naga curve. If the scale and angle that is varied approach a scale of one and an angle of 90° then the fractal formed approaches the Dragon curve of a scale of one with an angle of 90°. Conversely, if the scale and angle are varied away from one scale and angle of 90°, the fractal formed away from the Dragon curve of scale one with an angle of 90°. Keywords: Affine transformation, dragon curve, IFS method.